Phase 1 Study of the Safety, Tolerability, and Pharmacokinetics of Biapenem in Healthy Adult Subjects - Griffith, David C. (Antimicrob Agents Chemother, 2021)
The pharmacokinetics and safety of biapenem were studied in 36 healthy adult subjects in a randomized, placebo-controlled, double blind, sequential single- and multiple-ascending-dose study using doses from 250 to 1,250 mg administered three times a day using 3-h infusions. Maximum concentrations for biapenem were achieved at the end of the 3-h infusion. Biapenem exposure (area under the curve [AUC]) increased in a slightly greater-than-dose-proportional manner after single and multiple doses with no evidence of accumulation with multiple doses. Plasma AUCs increased from 18 mg · h/liter at 250 mg to 150 mg · h/liter at 1,250 mg. Urinary recovery ranged from 14.2% at 250 mg to 42.3% at 1,250 mg. Biapenem was well tolerated up to 1,000 mg administered every 8 h by a 3-h infusion for 7 days; however, higher incidences of nausea, vomiting, and rash were reported at 1,250 mg. There were no serious adverse events (AEs) reported after either single or multiple doses of biapenem, and all AEs were mild or moderate in severity. (This study has been registered at ClinicalTrials.gov under registration no. NCT01702649.)